Propuesta de Modelo de Sistema de Gestión de Calidad bajo la norma ISO 9001:2015 para la Empresa Martelec Arquitectura E Ingenieria S.A.S (2021)
The system of quality management based in the norm ISO 9001: 2015, present a set of requirements so that organizations implement the controls proposed and get as a result, the satisfaction of their customer needs, with high quality standards, through the implementation of the numerals present of 4 to 10, strategies are formulated, processes and alienations to get the expected results.